Mediating Role of Fluid Intelligence Between Working Memory and Academic Achievement of University Undergraduates: Does Gender Matter? - Niazi, Sadia; Adil, Adnan (Journal of Education and Educational Development, 2021)
The present study examined the mediating role of fluid intelligence between working memory (WM) and academic achievement and tested the invariance of this model across gender in a random sample of university students (N = 560, 228 boys & 332 girls). Heart and Flower task (Diamond, 2013) and Raven’s Standard Progressive MatricesTM Plus (Raven, 1998) were used to operationalize WM and fluid intelligence, respectively. Academic achievement was operationalized through the CGPAs of students. Findings of the path analysis suggested that fluid intelligence mediated between WM and CGPA. Test of the model invariance indicated that fluid intelligence was a stronger predictor of academic achievement for boys as compared to the girls, which suggested that the indirect effect of WM on academic achievement through fluid intelligence was stronger for boys. Significant gender differences were observed as girls’ mean scores on WM and academic achievement were higher than those of the boys.
Keywords: working memory, fluid intelligence, academic achievement, gender